FM 2009: Formal Methods Second World Congress, Eindhoven, The Netherlands, November 2-6, 2009, Proceedings - Cavalcanti, Ana; Dams, Dennis (Programming and Software Engineering,, 2009)
This book presents the refereed proceedings of FM 2009, the 16th International Symposium on Formal Methods, held as the Second World Congress on Formal Methods in Eindhoven, The Netherlands, in November 2009 in the course of the first International Formal Methods Week, FMWeek 2009. The 45 revised full papers presented together with 5 invited papers and 3 additional papers from the Industry Day were carefully reviewed and selected from 139 submissions. The papers are organized in topical sections on model checking, compositionality, verification, concurrency, refinement, static analysis, theorem proving, semantics, industrial applications, object-orientation, pointers, real-time, tools and industrial applications, and industry-day abstracts.